Analysis Of Industry-Based Tourism Human Resources Needs In The Super Priority Destination Area Of Lake Toba - Dalimunthe, Femmy Indriany; Ngatemin, Ngatemin; Rahmat, Rahmat; Emrizal, Emrizal (Jurnal Mamangan, 2023)
Lake Toba as a super priority destination is increasingly in demand by tourists, both local and foreign. Then several international events held at Lake Toba including F1H20 which received the attention of many domestic and foreign tourists and additionally in the near future in November 2023 there will be another international event including the Aquabike Jetski World Championship 2023. The purpose of this study is to increase the number of tourists and then it can be used as a supporter of the projection of the need for the number of tourism workers in the Lake Toba Super Priority Destination area. This study uses a qualitative research approach, the data source used in this study is a questionnaire or interview in collecting data, so the data source is called a respondent, namely a person who responds or answers written or oral questions. The results obtained In general, the need for workers in the tourism sector in 8 directly related districts is projected to increase. In meeting Tourism HR in the Lake Toba Super Priority Destination, it is necessary to prepare HR who have competence in the hotel and restaurant sector. We are sure that the existence of the Medan Tourism Polytechnic in preparing Tourism HR is good and has been qualified according to the needs of hotels and restaurants. Poltekpar Medan produces human resources, and PHRI absorbs human resources, we hope that Poltekpar Medan and PHRI will maintain a good relationship so that they continue to synergize in the future. As one of the fields in the tourism business, restaurants or eateries also need skilled workers to work. So in this study it is considered important to predict the number of workers needed for the next five years.